2009
DOI: 10.1080/02699200802399947
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception in children with speech output disorders

Abstract: Research in the field of speech production pathology is dominated by describing deficits in output. However, perceptual problems might underlie, precede, or interact with production disorders. The present study hypothesizes that the level of the production disorders is linked to level of perception disorders, thus lower-order production problems (such as childhood apraxia of speech; CAS) are linked to lower-order perception problems and higher-order production problems (phonological disorder; PD) are linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 19 publications
3
43
1
11
Order By: Relevance
“…Given suggestions that CAS involves a deficit in auditory and/or somatosensory feedback processing [8991] and some indication for impaired auditory perception in CAS [92,93], several recent CAS treatment studies aimed to enhance treatment by supplementing auditory and verbal feedback with visual feedback [94,95•]. The rationale is that children with CAS may utilize feedback provided through a different modality to improve their speech movements.…”
Section: Motor-based Treatment Approachesmentioning
confidence: 99%
“…Given suggestions that CAS involves a deficit in auditory and/or somatosensory feedback processing [8991] and some indication for impaired auditory perception in CAS [92,93], several recent CAS treatment studies aimed to enhance treatment by supplementing auditory and verbal feedback with visual feedback [94,95•]. The rationale is that children with CAS may utilize feedback provided through a different modality to improve their speech movements.…”
Section: Motor-based Treatment Approachesmentioning
confidence: 99%
“…Those authors also suggested a possible causal relation between an inability of auditory discrimination and phonological disorders that, however, did not apply to all cases they assessed. This relation was also mentioned by another author 8 . However, there seems to have an inconsistency in the literature regarding the association of deficits in the auditory production and discrimination.…”
Section: Figure 4 -Errors Total By Minimal Pairs In the Stop Voicinmentioning
confidence: 60%
“…Before the first words or phonemes begin to be produced, the child perceives and understands a lot more speech than he/she actually produces. Thus, the development of speech is closely related to auditory perception 8 . The auditory perception, in turn, can be subdivided into several components such as: detection, sound sensation, discrimination, location, recognition, understanding, attention and memory 2 .…”
mentioning
confidence: 99%
“…The problems are often systematic across the child's speech and affect phonological patterns rather than single speech sounds. For example, a child can display patterns of devoicing of stops, velar fronting, or consonant cluster reductions (Nijland, 2009). However, the child's phonological problems are rarely limited to the production of speech, but are often accompanied by difficulties in perception (Bird & Bishop, 1992;Rvachew, 1994).…”
Section: Introductionmentioning
confidence: 99%